6-(2p+3)+5(p-1)=

Simple and best practice solution for 6-(2p+3)+5(p-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(2p+3)+5(p-1)= equation:


Simplifying
6 + -1(2p + 3) + 5(p + -1) = 0

Reorder the terms:
6 + -1(3 + 2p) + 5(p + -1) = 0
6 + (3 * -1 + 2p * -1) + 5(p + -1) = 0
6 + (-3 + -2p) + 5(p + -1) = 0

Reorder the terms:
6 + -3 + -2p + 5(-1 + p) = 0
6 + -3 + -2p + (-1 * 5 + p * 5) = 0
6 + -3 + -2p + (-5 + 5p) = 0

Reorder the terms:
6 + -3 + -5 + -2p + 5p = 0

Combine like terms: 6 + -3 = 3
3 + -5 + -2p + 5p = 0

Combine like terms: 3 + -5 = -2
-2 + -2p + 5p = 0

Combine like terms: -2p + 5p = 3p
-2 + 3p = 0

Solving
-2 + 3p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 3p = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 3p = 0 + 2
3p = 0 + 2

Combine like terms: 0 + 2 = 2
3p = 2

Divide each side by '3'.
p = 0.6666666667

Simplifying
p = 0.6666666667

See similar equations:

| 4d-11=2y+7 | | 3x+5=81 | | 42/12=14/n | | 5c=65 | | 15=10+1.5x | | 7-x=31-7x | | -3h+12-4h=7h-9-16 | | 15x=10+1.5x | | 12/36=p/100 | | a+5=13 | | 17h+31=558 | | x+6=20/2 | | 8p*8p-4p=0 | | -3+(-9)= | | Z/6-3=4 | | 16/28=4/x | | 7+3d-5=-1+2d-12-d | | 5y+14=2(5y+6) | | x+(-6)=20/2 | | 8x-14=6x-11+x | | 8/15=x/45 | | x+12=-40 | | 15=10x+1.5x | | 20x-20=14x+22 | | 14/17=35/n | | x/8+7=24 | | -1-8(3x-4x)=31 | | 6a+14a=180 | | 48/-3 | | 4-8m=57 | | 5-9[2-(2y-8)]= | | 3x+1=4x+11 |

Equations solver categories